Safety, tolerability, pharmacokinetics and neutrophil elastase inhibitory effects of Sivelestat: A randomized, double-blind, placebo-controlled single- and multiple-dose escalation study in Chinese healthy subjects - Li, Kun; Dong, Lingfang; Gao, Shan; Zhang, Jingying; Feng, Yinghua; Gu, Li; Yang, Jie; Liu, Xing; Wang, Yaqin; Mao, Zhenkun; Jiang, Dandan; Xia, Zhengchao; et al. (European journal of pharmaceutical sciences, 2024)
•Sivelestat was safe and well tolerated during the dose escalation process.•The pharmacokinetic parameters Cmax and AUC increased in a dose dependent manner.•The accumulation of Cmax and AUC was not obvious after multiple doses.•The Cmin_ss in multiple-dose cohort could meet the needs of clinical treatment.•This work provided support for more diverse dosing regimen in clinical application. : Neutrophil elastase has been identified as a potential therapeutic target for acute lung injury or acute respiratory distress syndrome, and Sivelestat is a selective, reversible and competitive neutrophil elastase inhibitor. This study was designed to investigate the safety, tolerability, pharmacokinetics and neutrophil elastase inhibitory effects of Sivelestat in healthy Chinese subjects. : A randomized, double-blind, placebo-controlled single- and multiple-dose escalation clinical trial was carried out. Briefly, healthy volunteers in twelve cohorts with 8 per cohort received 1.0–20.2 mg/kg/h Sivelestat or placebo in an intravenous infusion manner for two hours, and healthy volunteers in four cohorts received two hours intravenous infusion of 2.0–5.0 mg/kg/h Sivelestat or placebo with an interval of twelve hours for seven times. The safety and tolerability were evaluated and serial blood samples were collected for pharmacokinetics and neutrophil elastase inhibitory effects analysis at the specified time-point. : A total of 128 subjects were enrolled and all participants completed the study except one. Sivelestat exhibited satisfactory safety and tolerability up to 20.2 mg/kg/h in single-dose cohorts and 5.0 mg/kg/h in multiple-dose cohorts. Even so, more attention should be paid to the safety risks when using high doses. The Cmax and AUC of Sivelestat increased in a dose dependent manner, and Tmax was similar for different dose cohorts. In multiple-dose cohorts, the plasma concentrations reached steady state 48 h after first administration and the accumulation of Cmax and AUC was not obvious. Furthermore, the Cmin_ss of 5.0 mg/kg/h dose cohort could meet the needs of clinical treatment. For some reason, the pharmacodynamics data revealed that the inhibitory effect of Sivelestat on neutrophil elastase content in healthy subjects was inconclusive. : Sivelestat was safe and well tolerated with appropriate pharmacokinetic parameters, which provided support for more diverse dosing regimen in clinical application. : www.chinadrugtrials.org.cn identifier is CTR20210072. [Display omitted] A randomized, double-blind, placebo-controlled single- and multiple-dose escalation clinical study was performed to explore alternative dosing regimen of Sivelestat.